Assessing Optimal Number of Stock Holdings on the Basis of Fund Market Performance - Obode, Ebikweluye (2010)
Since the early 1900s, the global mutual fund industry has experience rapid expansion. This is the direct result of an increase in investments via mutual funds thus making this investment vehicle a key player in the financial world. It is therefore no surprise that many academic studies on how to ensure effective fund performance have continued to grace the pages of finance journals. Amongst the most crucial decisions most mutual fund managers have to make is the number of stocks to hold. Some researchers believe that there is an optimal number of stocks for every mutual fund which is a reflection of the marginal difference between the benefits of diversification and its costs. Using the funds’ Sharpe ratio to represent performance, a significant relationship was found between the number of the stock holdings and risk-adjusted returns for 1986 U.S domestic equity mutual fund portfolios over the period (from 2004 to 2009). Equally, changes in portfolio holdings over time were found to share a greater level of correlation with the investment returns of funds.